SPECIFIC CHARACTERISTICS OF TEACHING THE SCIENCE OF PARASITOLOGY IN MEDICAL UNIVERSITIES - N. A. Ruzikulova; Z. B. Islamova; G. M. Matkarimova; I. S. Zokhidova; M. N. Turakulova (Web of Journals Publishing, 2024)
The article provides information about the methods used in the teaching of the parasitology department at medical universities. It is emphasized that situational examples and independent works have a special place in strengthening students' knowledge. Emphasis is placed on the diagnosis and prevention of parasitic diseases using various forms of traditional and interactive hands-on training.
Keywords: parasitology, situational issues, independent work, helminth, infection, diagnostics.